Primary Aortoduodenal Fistula Caused by Tuberculous Aortitis Presenting as Recurrent Massive Gastrointestinal Bleeding - Tzung-Jiun Tsai; Hsien-Chung Yu; Kwok-Hung Lai; Gin-Ho Lo; Ping-I Hsu; Ting-Ying Fu (Journal of the Formosan Medical Association, 2008)
Upper gastrointestinal bleeding from primary aortoduodenal fistula (PADF) is unusual and fatal. The etiology of PADF from tuberculous aortitis is rare. We report a 69-year-old male patient who suffered recurrent hematemesis and hematochezia with hypovolemic shock of unknown origin. Initial endoscopy failed to lead to a diagnosis. A bleeder over the third portion of the duodenum was found after the third endoscopy. Exploratory laparotomy showed a ruptured aortic pseudoaneurysm with an aortoduodenal fistula. Dacron graft repair of the aorta and simple closure of the duodenal fistula were carried out. Pathologic examination revealed tuberculous aortitis. The patient survived and was symptom-free following operation and antituberculous therapy. Review of the literature revealed that the clinical presentations in this disorder are insidious. The endoscopic findings are atypical. We conclude that so-called “herald bleeding”, a history of tuberculous infection or aortic aneurysm and a high degree of suspicion are critical for successful diagnosis. Early diagnosis and surgical exploration are needed for timely and successful management.